Pemanfaatan Ekstrak Limbah Pasar Buah Dan Sayuran Sebagai Pengganti Vaksin Serta Pemacu Pertumbuhan: Utilization of Fruit and Vegetable Market Waste Extracts as a Substitute for Vaccines and Growth Boosters (Jurnal Riset Agribisnis dan Peternakan, 2024)
Village chickens are usually kept by the community to meet the family's protein intake needs, either from eggs or meat. The chicken is easy to maintain, the meat and eggs are delicious and contain high nutrition and are safe for health. One type of free-range chicken is the Balitnak Superior Chicken (KUB). These chickens excel in egg production, uniform growth and disease resistance. However, farmers continue to prevent disease by providing vaccinations or vitamins. Based on this, a research was carried out by utilizing vegetable and fruit waste which was used as probiotics rich in lactic acid bacteria (LAB). The purpose of this research is not only to look at the potential of market waste for fermented vegetables and fruits, but also to determine the effect of the fermented products on livestock, both on productivity and health levels, as seen from the size of the lymphoid organs. The results of the study are the potential of vegetable and fruit market waste to be a source of lactic acid bacteria which has the potential to be a probiotic for chickens. The content of lactic acid bacteria affects feed consumption but not for drinking water consumption and body weight gain. Based on this, it can be concluded that the use of fermented vegetable and fruit market waste can be an alternative to probiotics and stimulate growth and reduce the dependence of farmers on the use of chemical vaccines.
Keywords: free-range chicken, vegetable market waste, fruit, fermentation, probiotics